"For Now, We Are in Waiting": Negotiating Time in Chile's Social Housing System. (17th April 2018) - Koppelman, Carter M.
Abstract: Waiting for low‐income housing is an increasingly common experience of the urban poor in both the global North and South, although little attention has been paid to its effects. Engaging a growing literature on time in systems of social provision, this article presents an ethnographic case study of waiting among poor housing‐seekers in a peripheral district of Santiago, Chile. While illustrating how waiting is produced by state policies and practices that position homeless city‐dwellers as passive clients, it challenges existing studies that argue that waiting produces durable submission to dominant state projects. In contrast, it shows that housing‐seekers in Santiago actively negotiated a denigrating temporality of state provision through multiple practices, including collective contestation of arbitrary delays. By dissecting the conditions that enabled contentious responses to waiting for housing in Chile, this article aims to elucidate how such temporal contestation may emerge (or be precluded) in other contexts.